Crystallization and preliminary X‐ray diffraction studies of the (R)‐selective amine transaminase from Aspergillus fumigatus. Issue 12 (1st December 2013) - Thomsen, Maren; Skalden, Lilly; Palm, Gottfried J.; Höhne, Matthias; Bornscheuer, Uwe T.; Hinrichs, Winfried
<x xml:space="preserve">Abstract</x> The (R)‐selective amine transaminase from Aspergillus fumigatus was expressed in Escherichia coli and purified to homogeneity. Bright yellow crystals appeared while storing the concentrated solution in the refrigerator and belonged to space group C2221. X‐ray diffraction data were collected to 1.27 Å resolution, as well as an anomalous data set to 1.84 Å resolution that was suitable for S‐SAD phasing.